Zooplankton sampling during the 56th Japanese Antarctic Research Expedition in austral summer 2014–2015 - TAKAHASHI, Kunio T.; TAKAMURA, Tomomi R.; IIDA, Takahiro; ODATE, Tsuneo (国立極地研究所, 2016)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0018.doc Fig. 2 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0019.doc Fig. 3 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0020.doc Fig. 4 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0021.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0022.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0023.doc Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0024.doc Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0025.doc Table 5 | http://polaris.nipr.ac.jp/~parc/pub/v023/nipr_parc_175_0026.doc departmental bulletin paper